Challenges of Air-Lines’ Development on the Basis of their Accounting Book Analysis - D. V. Lysenko; L. Akgьn (Вестник Российского экономического университета имени Г. В. Плеханова)
The article studies the work of Russian air-lines in the current situation of unstable market of air-transportation. The public company ‘Aeroflot’, the industry leader acts as an object of the research. Topicality of the subject is explained by strategic importance of the company development in Russia, as the growth in air-transportation acts as a great stimulus for the Russian economy development. The authors analyzed finance figures of air-lines that show efficiency of their work and came to the conclusion about key reasons of their fluctuations in today’s conditions. On the basis of comparative analysis they identified the air-line, which managed to retain certain finance stability. The article also studies current trends of air-transportation market and on their foundation worked out recommendations by vectors of air-lines’ development. The algorithm of drawing respective conclusions about airlines’ stability and their efficiency was shown by factor analysis of finance figures. Calculations made by the authors according to the proposed methodology of economic analysis are logically substantiated. In article preparation the authors used normative documents, present day literature sources dealing with the subject of the research, articles of academic journals and annual accounting reports of companies. Analysis methodology provided in the article could allow experts to improve the quality of analytical work in the field of economic analysis of air-lines’ operation and optimization of principle figures of their economic functioning.